Nucleation during boiling, with special reference to its cessation at low pressure - Jawurek, Harald Hans (Department of Chemical Engineering, 2016)
A critical review of the mechanisms, models and heat-transfer correlations for nucleate boiling is presented. The importance of nucleation is stressed. It is pointed out that the bulk of correlations are based on the erroneous notion that the energy transferred away from the heating surface by bubbles as such, in the form of latent heat, contributes insignificantly to the total flux. - A critical review of the correlations for the upper limit of the nucleate boiling regime - the peak flux is also presented. The theory of nucleation during boiling is reviewed and extended in an attempt to explain the complete absence of the nucleate regime, noted in preliminary tests conducted at low pressures.